2010
DOI: 10.1074/jbc.m110.134221
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Barbed End Uncapping by CARMIL Homology Domain 3 of Mouse CARMIL-1

Abstract: Capping protein (CP) is a ubiquitously expressed, 62-kDa heterodimer that binds the barbed end of the actin filament with ϳ0.1 nM affinity to prevent further monomer addition. CARMIL is a multidomain protein, present from protozoa to mammals, that binds CP and is important for normal actin dynamics in vivo. The CARMIL CP binding site resides in its CAH3 domain (CARMIL homology domain 3) located at or near the protein's C terminus. CAH3 binds CP with ϳ1 nM affinity, resulting in a complex with weak capping acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 56 publications
4
48
0
Order By: Relevance
“…A subsequent allosteric change in CP caused by ternary complex formation then drives V-1 dissociation, yielding the CP:CAH3 complex. Importantly, the binding sites on the surface of CP for CAH3 and V-1 are nonoverlapping, consistent with the possibility that these three proteins form a ternary complex (17)(18)(19)(20)(21).…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…A subsequent allosteric change in CP caused by ternary complex formation then drives V-1 dissociation, yielding the CP:CAH3 complex. Importantly, the binding sites on the surface of CP for CAH3 and V-1 are nonoverlapping, consistent with the possibility that these three proteins form a ternary complex (17)(18)(19)(20)(21).…”
mentioning
confidence: 57%
“…In the last step (step 4), 2 μM monomeric actin [containing 20% tetramethylrhodamine-5-maleimide (TMR)-labeled and 0.5% biotin-labeled actin], together with variable concentrations of CP (0-1 μM final) and a constant concentration of CAH3 (10 μM final), were added. Given CAH3's strong affinity for CP (1-3 nM) (17,19,25), this very high concentration of CAH3 should essentially preclude inhibition of actin polymerization by free CP. Fig.…”
Section: Cp:cah3 Complex Regulates the Rate Of Barbed-end Elongation mentioning
confidence: 99%
“…However, substantial portions of the CARMIL fragment were not resolved in the structure, raising the possibility that these unresolved regions might be in contact with one of the several actin-binding surfaces of CP. In addition, a separate structural study, utilizing NMR, concluded that certain residues of CARMIL were in close contact with residues of CP known to contact actin (36).…”
Section: Discussionmentioning
confidence: 99%
“…conformation that binds the barbed end weakly (23)(24)(25). Recent work suggests that CARMIL proteins function in vivo at the plasma membrane:cytoplasm interface of protruding edges, where they appear to be recruited, unfolded, and activated to promote actin assembly (26).…”
mentioning
confidence: 99%